Study of Hybrid Nano Particles Flow in an Inclined Circular Artery - Raja, Syed Waseem (Communications in Mathematics and Applications, 2025)
In the present article, steady fluid flow through an inclined tube of nonuniform cross section with stenosis and dilation has been investigated under the influence of hybrid nanofluid particles. The homotopy perturbation method is applied to solve the flow equations assuming mild stenosis to determine the axial velocity, wall shear stress, pressure gradient, and streamlines. Studies have examined how parameters effects on pressure gradient, impedance resistance λ and wall shear stress \(S_rz\).